An overview of the current state of OER movement in Saudi Arabia and the Arab World. (29th November 2010) - Al-Khalifa, Hend S.
Open educational resources (OER) is currently a worldwide growing trend fuelled by the advancement of the web. The wide adoption of this movement in languages such as Chinese, Japanese, Portuguese and many others shows how powerful and influential this movement has played. On the other hand, the Arab World suffers from a significant digital gap, and a serious shortage of Arabic OER that serve their educational and cultural needs. In this paper, we shed the light on the current movement of OER in the Arab World in general and in Saudi Arabia in particular as well as discussing the challenges and opportunities facing this movement in the Arab region.